A Study on the Indian Real Estate Market for Investment: A Qualitative Approach - Mehta, Rashi (2007)
This dissertation aims to evaluate the investment opportunities present in the Indian real estate market. The surveys and responses of the representatives of the real estate market have been analysed and the results of the study clearly establishes growth of the sector in the forthcoming years. Different aspects of the market have been examined such as the importance of India as an investment destination, hindrances in the market, sources of capital available, scope of the industry etc to get a deeper insight of the market. These factors have also helped to determine the factors to be considered before investment. New techniques of investment such as REITs (Real Estate Investment Trusts) have come to light inducing investors to plough their funds into the market to produce lucrative yet stable returns.